Pengaruh GCG, CSR, dan Kredit Hijau Terhadap Kinerja Keuangan Bank - Inka Pratiwi Khoirunnisa; Ninik Anggraini; Fitria Magdalena Suprapto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to test and analyze the influence of GCG, CSR, nd green credit on bank financial performance. This research was conducted on four banking companies obtained based on purposive sampling techniques. This research uses secondary data originating from company financial reports. SPSS tools were used to assist in analyzing research data. The results of this study state that GCG with the proxy of independent commissioners has no effect on bank financial performance, while the proxies for managerial ownership and institutional ownership have an effect on financial performance. CSR has no effect on bank financial performance. Green credit influences bank financial performance. Green credit moderating variables can strengthen the relationship between independent commissioners and institutional ownership. In the relationship between managerial ownership and CSR, the moderating variable green credit is not able to strengthen its relationship with bank financial performance.